4CPS-135 Effectiveness and cost of eculizumab on patients with atypical (shua), urenic and haemolitic syndrome, with enlargement of the frequency of administration - Cifuentes, S (Eur J Hosp Pharm, 2018)
BACKGROUND: Atypical haemolytic uraemic syndrome (aHUS) is a thrombotic microangiopathy that primarily affects the kidney. PURPOSE: To compare the effectiveness and cost of eculizumab (monoclonal antibody indicated for the treatment of aHUS) on a patient on whom it is administered more frequently as a strategy of therapeutical optimisation. MATERIAL AND METHODS: Retrospective study of adult patients with SHUa, treated with eculizumab 1200 mg each 14 days. Clinical variables of effectiveness were determined as: renal function (creatinine), haematologic function (platelets) and indicative parameters of haemolysis (lactate deshodrogenasa (LDH) and haptoglobina). Data were taken from the pharmacy program and from the clinical history of the patient. RESULTS: A male with suspicion of an outbreak compatible with aHUS that was begun with eculizumab, after persistence of renal insufficiency and haemolysis. After 20 doses his good renal response and normalisation of the rest of clinical variables permitted us to carry out a pharmacy-therapeutic optimisation through which the posology interval was extended to each 30 days. The average values obtained during that period, before enlarging the frequency, were: creatinine: 1.9 mg/dl; platelets: 150.109/L; LDH: 465 UI/L; haptoglobuline: 130 mg/dL, and the cost incurred from that monthly period was €31 100. After the change, he has received four doses and his analytic and clinic stability was maintained. The determined average values of creatinine, platelets, LDH and haptoglobuline were 1.47 mg/dL, 160.109/L, 337 UI/L, 136 mg/dL respectively, and the monthly cost was €15 550. CONCLUSION: Eculizumab has showed a significant renal improvement, avoiding progression to techniques of dialysis, a good haematologic response and improvement of intervascular haemolysis. The enlargement in the frequency of administration does not suppose a deterioration in the effectiveness, and it is observed that a monthly saving of €15 550 would suppose an annualy saving of €1 86 000. The pharmacy service must impose itself in introducing strategies to personalising treatments of high economic impact. No conflict of interest